Creep Behavior and Long-Term Deformation Prediction of Ground Reinforced by High-Permeability Grouting - Li Chenhui; Xu Zhipeng; Zhou Pengkun; Zhang Hongbo; Zheng Yantao; Li Runguo; Liu Changwu (工程科学与技术)
ObjectiveAlthough grouting reinforcement techniques are effective in significantly enhancing the bearing capacity of strata in the short term, the grouted bodies are prone to creep deformation under the combined influence of sustained loading and groundwater pressure. This phenomenon may lead to gradual surface settlement and structural instability, thereby compromising the long-term safety and performance of underground infrastructure. This study investigated the creep behavior of grouted bodies formed in highly permeable silt and sand–gravel strata under coupled axial load and hydraulic pressure. The objective was to systematically examine the creep mechanisms and deformation characteristics, thereby providing theoretical support and practical guidance for long-term stability assessments and deformation predictions of grouting-reinforced strata.MethodsFirstly, Silt and sand–gravel aggregates were collected from in-situ formations and packed into molds. A permeation grouting method was employed to simulate field grouting conditions. Following grout injection and initial setting, specimen surfaces were leveled and sealed, and specimens were cured for 28 days under controlled temperature and humidity. Uniaxial compressive strength (UCS) tests were then conducted to determine the peak strength of the grouted bodies, which served as a reference for subsequent creep loading schemes. Secondly, Creep tests were performed under long-term stepwise loading conditions using a pressurized chamber filled with water to apply confining pressure. Each load increment was maintained until creep deformation approached stabilization, after which the next load level was applied, continuing until specimen failure. Full creep curves were recorded throughout the process. The effects of stress level on deformation magnitude and creep rate were evaluated, and the long-term strength of the grouted bodies under coupled stress–seepage conditions was derived using the isochronous stress method. Finally, Experimental data were fitted using the Burgers model and a nonlinear viscoelastic–plastic model. Key creep parameters were extracted accordingly. A representative numerical model of the grouted stratum was developed using actual site parameters and implemented in COMSOL Multiphysics to simulate long-term settlement behavior under coupled mechanical–hydraulic conditions.Results and Discussions　The creep tests revealed that the time-dependent deformation behavior of the grouted bodies was strongly stress-dependent, with evident stress thresholds identified at 2.3 MPa for silt and 3.4 MPa for sand–gravel. Below these thresholds, specimens mainly exhibited decelerating and steady-state creep, with a gradually decreasing strain rate. In contrast, when the applied stress exceeded the thresholds, accelerated creep occurred, characterized by continuously increasing axial strain and eventual failure. Significant increases in total axial strain were observed once the stress surpassed the threshold: from 0.2% to 0.403% in silt, and from 0.091% to 0.458% in sand–gravel. These results indicate a substantial risk of secondary failure in grouted strata under sustained high stress, emphasizing the necessity of incorporating creep effects in design and long-term performance evaluations. Increased loading not only delayed the onset of steady-state creep but also amplified the long-term creep rate. At stress levels of 1.5 MPa and 1.8 MPa, steady-state creep rates approached zero. However, at 2.3 MPa and 3.4 MPa, steady-state creep rates increased significantly, reaching approximately 0.2×10⁻⁴/h. This increase in creep rate under high stress conditions exacerbates the risk of long-term instability. The isochronous stress–strain curves displayed a linear trend under low stress conditions, transitioning to nonlinear behavior with distinct inflection points when the stress exceeded the threshold. These inflection points correspond to the long-term strength limits of the grouted bodies. Comparisons with actual site loading conditions indicated that operational stresses remained below these limits, suggesting that the grouted strata would remain stable over extended service periods. Both the Burgers and nonlinear viscoelastic–plastic models provided accurate fits to the experimental creep data across all stress levels, with coefficients of determination (R²) exceeding 0.95. Post-grouting settlement curves demonstrated the effectiveness of grouting in mitigating short-term deformation. Numerical simulations showed a high initial settlement rate that progressively attenuated over time. After 50 years, settlement magnitudes at monitoring points were 8 mm, 9 mm, 19 mm, and 24 mm, all remaining below the critical threshold of 25 mm. These findings validate the long-term stability of the grouted strata and confirm that reactivation of settlement failure is unlikely in treated zones.ConclusionsCreep tests under stepwise loading were conducted on grouted bodies formed in highly permeable silt and sand–gravel strata. The results revealed that high stress levels significantly increased creep deformation and posed potential threats to the stability of grouted formations. Therefore, the creep behavior of grouted strata should be thoroughly considered in engineering design and service-life assessments. Numerical simulations incorporating laboratory-derived creep parameters confirmed that the treated strata are expected to maintain long-term stability without recurrence of settlement-induced failure.